Pengaruh Brand Awareness dan Brand Image Terhadap Keputusan Pembelian Pada Produk Skincare The Originote Pada Mahasiswa Jurusan S1 Manajemen Universitas Dharma Andalas - Marnia Sarah; Nofri Yendra (CV. ITTC INDONESIA, 2025)
This research aims to analyze the influence of brand awareness and brand image on purchase decisions of The Originote skincare products among undergraduate management students at Universitas Dharma Andalas. The background of this study is the increasing use of skincare among students and the tight competition among local brands, which require companies to build strong brand awareness and a positive brand image to attract consumers. The research method used is quantitative, with questionnaires distributed to 108 student respondents. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The results show that brand awareness has a positive and significant effect on purchase decisions, brand image also has a positive and significant effect on purchase decisions, and both variables together have a significant influence on purchase decisions of The Originote skincare products.In conclusion, the higher the brand awareness and brand image, the greater the possibility that students will decide to purchase The Originote skincare products.